2021
DOI: 10.1177/87552930211003916
|View full text |Cite
|
Sign up to set email alerts
|

Ground motions in urban Los Angeles from the 2019 Ridgecrest earthquake sequence

Abstract: We study ground-motion response in urban Los Angeles during the two largest events (M7.1 and M6.4) of the 2019 Ridgecrest earthquake sequence using recordings from multiple regional seismic networks as well as a subset of 350 stations from the much denser Community Seismic Network. In the first part of our study, we examine the observed response spectral (pseudo) accelerations for a selection of periods of engineering significance (1, 3, 6, and 8 s). Significant ground-motion amplification is present and repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…We used the components of the CSN located within the northeast LA basin, which is the densest part of the array -the study area, including the locations of the stations, is shown in Figure 2. Various display of the Ridgecrest earthquake data are shown in Filippitzis et al (2021), along with a comparison of the data and predicted ground motions by several methods. For our study, data were first detrended, rotated into the ZRT frame, decimated to 5 Hz and then detrended once more.…”
Section: Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the components of the CSN located within the northeast LA basin, which is the densest part of the array -the study area, including the locations of the stations, is shown in Figure 2. Various display of the Ridgecrest earthquake data are shown in Filippitzis et al (2021), along with a comparison of the data and predicted ground motions by several methods. For our study, data were first detrended, rotated into the ZRT frame, decimated to 5 Hz and then detrended once more.…”
Section: Preprocessingmentioning
confidence: 99%
“…In contrast, CVM-S is significantly smoother than CVM-H due to its reliance on wavefield-tomography during the final stages of construction, although several sharp resolution based artefacts are also evident. While many features of the seismic wavefield within the LA basin, such as phase arrival times and P-to-S amplitude ratios, are captured for local events at frequencies of up to 0.2 Hz (Taborda et al, 2016;Lai et al, 2020), excitations of the basin from the recent large regional Ridgecrest earthquake sequence in July 2019 have illustrated that ground motion amplification predictions from finite-difference wave propagation through the SCEC CVM-H and CVM-S models do not accurately model the observations even at the relatively low frequency 0.1-1Hz range that is relevant for tall buildings within downtown LA (Filippitzis et al, 2021), warranting continued close study of the LA basin velocity model. Seismic tomography offers the best opportunity for full spatial coverage of the basin at high resolution, especially when dense seismic arrays are utilized.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many features of the seismic wavefield within the LA basin, such as phase arrival times and P-to-S amplitude ratios, are captured for local events at frequencies of up to 0.2 Hz (Taborda et al, 2016;Lai et al, 2020). However, excitations of the basin from the recent large regional Ridgecrest earthquake sequence in July 2019 have illustrated that ground motion amplification predictions from finite-difference wave propagation through the SCEC CVM-H and CVM-S models do not accurately predict the observations in the 0.1-1 Hz range that is relevant for tall buildings within downtown LA (Filippitzis et al, 2021) ing off-the-shelf components, and have a maximum observable acceleration of ±2g, in order to fulfil their primary goal of strong-ground-motion monitoring. As a result, the instrument noise floor is above the amplitude of ground motions produced by smaller regional earthquakes, and is also above the am- both the CVM-H and CVM-S models (Graves, 1996).…”
Section: Accepted Articlementioning
confidence: 99%
“…Many features of the seismic wavefield within the LA basin, such as phase arrival times and P‐to‐S amplitude ratios, are captured for local events at frequencies of up to 0.2 Hz (Lai et al., 2020; Taborda et al., 2016). However, excitations of the basin from the recent large regional Ridgecrest earthquake sequence in July 2019 have illustrated that ground motion amplification predictions from finite‐difference wave propagation through the SCEC CVM‐H and CVM‐S models do not accurately predict the observations in the 0.1–1 Hz range that is relevant for tall buildings within downtown LA (Filippitzis et al., 2021), warranting continued close study of the LA basin velocity model.…”
Section: Introductionmentioning
confidence: 99%